Uterine leiomyomas: correlation between histologic composition and stiffness via magnetic resonance elastography — a Pilot Study - Obrzut, Marzanna (Ginekol Pol, 2020)
OBJECTIVES: To evaluate magnetic resonance elastography as a tool for characterizing uterine leimyomas. MATERIAL AND METHODS: At total of 12 women with symptomatic leiomyomas diagnosed in physical and ultrasound examinations were enrolled in this pilot study. Before surgery, all patients underwent magnetic resonance elastography of the uterus using a 1.5 T MR whole-body scanner (Optima, GE Healthcare, Milwaukee, WI, USA). Surgical specimens were forwarded for histological examination. The findings were allocated into 3 categories depending on the percentage content of connective tissue: below 15%, from 15 to 30% and more than 30%. The median stiffness of leiomyomas for each of the group was calculated. The U-Mann Whitney test was used for statistical analysis. RESULTS: The stiffness of the leiomyomas ranged between 3.7–6.9 kPa (median value 4.9 kPa). The concentration of extracellular components in the leiomyomas did not exceed 40%. An increasing trend of the stiffness with the growing percentage of extracellular component was observed. Stiffness of the leiomyomas obtained by MRE varies depending on microscopic composition. CONCLUSIONS: The value of stiffness shows a trend of increasing with the percentage of extracellular component of the leiomyoma. Further studies are required to assess the usefulness of MRE in diagnostics of uterine leiomyomas.